2022
DOI: 10.2196/30885
|View full text |Cite
|
Sign up to set email alerts
|

US Black Maternal Health Advocacy Topics and Trends on Twitter: Temporal Infoveillance Study

Abstract: Background Black women in the United States disproportionately suffer adverse pregnancy and birth outcomes compared to White women. Economic adversity and implicit bias during clinical encounters may lead to physiological responses that place Black women at higher risk for adverse birth outcomes. The novel coronavirus disease of 2019 (COVID-19) further exacerbated this risk, as safety protocols increased social isolation in clinical settings, thereby limiting opportunities to advocate for unbiased … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…One of the critical issues maternal health advocates are addressing is the lack of access to high-quality maternal care, particularly in Black communities [6,25]. More than 50% of US counties are without a practicing obstetrician, and many rural hospitals have closed their obstetric units due to financial challenges [26].…”
Section: Maternal Mortality Advocacy In the United Statesmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the critical issues maternal health advocates are addressing is the lack of access to high-quality maternal care, particularly in Black communities [6,25]. More than 50% of US counties are without a practicing obstetrician, and many rural hospitals have closed their obstetric units due to financial challenges [26].…”
Section: Maternal Mortality Advocacy In the United Statesmentioning
confidence: 99%
“…For instance, one study investigated the feasibility of using Twitter to identify public discourse on maternal health among Black women across the United States. The study revealed that Twitter is a valuable source for providing a snapshot of relevant topics to guide Black maternal health advocacy efforts [6]. There is a need to examine how advocacy groups use Twitter to raise awareness about US maternal mortality in ways that quantitative research cannot fully explore.…”
Section: Maternal Mortality Advocacy In the United Statesmentioning
confidence: 99%
See 2 more Smart Citations